SYNTHESIS OF P38 MAP KINASE INHIBITOR ANALOGUES COMPOUNDS AND QUINOXALINONE DERIVATIVES - KUO CHU HWANG,; PERIYASAMY MURUGAN, (International Journal of Pharma and Bio Sciences, 2014)
This paper reports the synthesis of nitrogen containing heterocyclic compounds such as quinoxalines (5-7), imidazoles (8, 9,10,11), aminothiazole (12), aminooxazole (13), aminoimidazole (14) and benzothiazine (17) from the reaction with unsymmetrical diketone 4, 3 and 4a respectively. The aforementioned compounds with 4-pyridyl,4-fluorophenyl groups have different positions in their ring skeleton. The quinoxalinone derivatives (19, 20) were synthesized by the reaction of (18) with o-phenylenediamine and 4,5-dimethyl- o-phenylenediamine respectively.